2003
DOI: 10.1021/ja034050q
|View full text |Cite
|
Sign up to set email alerts
|

Dihydrogen-Bond-Promoted Catalysis:  Catalytic Hydration of Nitriles with the Indenylruthenium Hydride Complex (η5-C9H7)Ru(dppm)H (dppm = Bis(diphenylphosphino)methane)

Abstract: The indenylruthenium hydride complex (eta(5)-C(9)H(7))Ru(dppm)H was found to be active in catalyzing the hydration of nitriles to amides. The chloro analogue (eta(5)-C(9)H(7))Ru(dppm)Cl was, however, found to be inactive. Density functional theory calculations at the B3LYP level provide explanations for the effectiveness of the hydride complex and the ineffectiveness of the chloro complex in the catalysis. It is learned that the presence of a Ru-H.H-OH dihydrogen-bonding interaction in the transition state low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
59
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(63 citation statements)
references
References 53 publications
(23 reference statements)
4
59
0
Order By: Relevance
“…These complexes have been implicated as intermediates in a variety of reactions, such as hydrogenation and hydroformylation [12][13][14][15], and can be found in biological systems, such as nickel-dependent hydrogenase enzymes [16], and in industry [17]. The discovery of the dihydrogen bond (M-H Á Á Á H-X, where M ¼ transition metal or boron; X ¼ N, O, F) has reinvigorated the field of hydride chemistry [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…These complexes have been implicated as intermediates in a variety of reactions, such as hydrogenation and hydroformylation [12][13][14][15], and can be found in biological systems, such as nickel-dependent hydrogenase enzymes [16], and in industry [17]. The discovery of the dihydrogen bond (M-H Á Á Á H-X, where M ¼ transition metal or boron; X ¼ N, O, F) has reinvigorated the field of hydride chemistry [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…It has *Corresponding author. E-mail: liqingzhong1990@sina.com been demonstrated that dihydrogen bonds can influence structure, reactivity, and selectivity in solution and solid state [1,14,15], thus having potential utility in catalysis [16,17], crystal engineering and materials chemistry [18].…”
Section: Introductionmentioning
confidence: 99%
“…The role of negatively charged hydrogen was also found in the so‐called charge‐inverted hydrogen bonds32, 33 and hydride bonds 34. This means that the halogen‐hydride interaction has similar roles in stabilizing metal complexes,35 controlling reactivity and selectivity of chemical reactions,36 promoting catalytic reactions,37 and mediating proton transfer38 like dihydrogen bonds. This interaction is rare, although it was found in the Cambridge Structural Database 25.…”
Section: Introductionmentioning
confidence: 92%